Phospholipase PlcH is involved in the secretion of cell wall glycoproteins and contributes to the host immune response of Aspergillus fumigatus - Jinbin Hao; Yin Guo; Hui Zhou; Haomiao Ouyang; Jinghua Yang; Wenxia Fang; Cheng Jin (mLife)
Abstract Glycosylphosphatidylinositol (GPI) anchoring is one of the conserved posttranslational modifications in eukaryotes that attach proteins to the plasma membrane. In fungi, in addition to plasma membrane GPI‐anchored proteins (GPI‐APs), some GPI‐APs are specifically released from the cell membrane, secreted into the cell wall, and covalently linked to cell wall glucans as GPI‐anchored cell wall proteins (GPI‐CWPs). However, it remains unclear how fungal cells specifically release GPI‐CWPs from their membranes. In this study, phospholipase PlcH was identified and confirmed as a phospholipase C that hydrolyzes phosphate ester bonds to release GPI‐APs from the membrane of the opportunistic fungal pathogen Aspergillus fumigatus. Deletion of the plcH gene led to abnormal conidiation, polar abnormality, and increased sensitivity to antifungal drugs. In an immunocompromised mouse model, the ΔplcH mutant showed an attenuated inflammatory response and increased macrophage killing compared with the wild type. Biochemical and proteomic analyses revealed that PlcH was involved in the localization of various cell wall GPI‐APs and contributed to the cell wall integrity. Our results demonstrate that PlcH can specifically recognize and release GPI‐CWPs from the cell membrane, which represents a newly discovered secretory pathway of GPI‐CWPs in A. fumigatus.